Hierarchy of Branding of Abandoned Animal Protection Organizations: The Case of Animal Defender Indonesia - Livo Februsa; Mulyadi (Graduate School of Communication Universitas Bakrie, 2022)
This paper explores the branding strategies of Animal Defenders Indonesia (ADI), an organization dedicated to rescuing and protecting neglected animals. With a focus on the AKIELS model—spanning Brand Awareness to Brand Spirituality—the study evaluates ADI's positioning in animal protection. Beginning with an overview of the prevalence of pet neglect, the paper introduces ADI as a critical player founded in 2011 to address the challenges faced by abandoned and injured animals in Indonesia. ADI's multifaceted approach, encompassing Rescue, Rehab, Rehome, and Education, forms the foundation of its mission to save and protect animals, particularly those subjected to abandonment, injury, or abuse. The organization also emphasizes public awareness through educational initiatives. The paper then delves into the AKIELS framework, analyzing ADI's branding strategies across various platforms. Drawing on previous research, the study highlights the role of social media in ADI's communication strategies, notably successful campaigns like